The Role of E-Government in combating Corruption in Syria - Zaher, Animar Ali (Journal of Economic, Administrative and Legal Sciences, 2025)
This research examines the role of electronic administration in combating administrative corruption in Syria. Administrative corruption is one of the major obstacles to development and negatively impacts the efficiency of government institutions. The study defines electronic administration, its significance, and its goals in promoting transparency and reducing administrative violations through the adoption of modern digital systems.The research explores key electronic administration tools such as digital governance, electronic archiving, digital signatures, and smart monitoring systems, which help minimize human intervention and limit corruption opportunities. It also reviews successful international experiences in implementing electronic administration and their impact on enhancing integrity and transparency.The study emphasizes that the success of electronic administration in Syria requires developing a comprehensive digital infrastructure, enacting supportive legislation, and training administrative staff to utilize modern technologies. Additionally, it highlights the importance of collaboration between the public and private sectors to ensure an effective and sustainable digital transformation.
Keywords: E-Government; Administrative Corruption; Digital Transformation; Governance; Transparency; Integrity; Syria; Electronic Signature